Analytic assessment of writing: diagnosing areas of strength and weakness in the writing of TESL undergraduate students - Ahour, Touran; Mukundan, Jayakaran (EBSCO Publishing, 2009)
The aim of this study was to find out the contribution of each writing component to the variance of overall writing performance. Writing samples were collected from 128 students majoring in Teaching English as a Second Language at Universiti Putra Malaysia. The analytic scoring scale of Weir (1990) was employed by two independent raters for rating the writing samples on two comparable prompts. The stepwise regression analysis indicated the high contribution of Grammar to the variance of total writing scores followed by cohesion, vocabulary, spelling, punctuation, and content respectively. It is found that component of Organization had the lowest amount of contribution to the overall writing variance. The result reflected the weakness of the students basically in the components of Grammar and Cohesion. The findings reveal the positive impact of analytical scoring scales in instructional situations in terms of diagnosing areas of students’ weaknesses and strengths in writing.